(untitled) (Academia Journal of Medicine, 2024)
Cone Beam Computed Tomography (CBCT) represents a significant advancement in the field of Oral Medicine, offering three-dimensional imaging that provides detailed anatomical information. This imaging technique has revolutionized the way clinicians diagnose, plan treatment, and manage a wide range of dental and maxillofacial conditions. The applications of CBCT in Oral Medicine are vast, ranging from implantology and orthodontics to endodontics and maxillofacial surgery. This paper explores the key applications of CBCT in oral health care, emphasizing its advantages over traditional two dimensional imaging techniques, and discusses the implications of its use in clinical practice.